(untitled) (World Bulletin of Public Health, 2024)
100 patients with DE stages I-III were examined to determine the characteristics of cognitive and emotional disorders in dyscirculatory encephalopathy, 70 women and 30 men (average age 62.4±14.9). The etiological basis for the development of DE in the examined patients was atherosclerosis (29.1%), arterial hypertension (22.2%), their combination (37.7%) and arterial hypotension (11%). At the first stage of DE, there is a discrepancy between subjective and objective assessments of cognitive functions, which indicates both the lability of mental functions, flickering symptoms characteristic of cerebral vascular disorders, and the presence of an asthenic symptom complex. Under the influence of age, attention and visual memory suffer more. According to the "Exclusion of excess" method, significant differences were also obtained, indicating that the decrease in semantic memory continues to increase with age.